Agave garciaruizii (Asparagaceae) a new species from the Chorros del Varal State Reserve in western Mexico - Hernández-Vera, Gerardo; Vázquez-García, J. Antonio; Padilla-Lepe, Jesús; Nieves-Hernández, Gregorio (Phytotaxa, 2019)
A new species named Agave garciaruizii is described and illustrated here. A. garciaruizii is endemic to tropical dry forest in the Itzícuaro and Apupátaro river canyons in the Chorros del Varal State Reserve, at the southern border of the states of Jalisco and Michoacán, México. It belongs to the subgenus Littaea and to the Marginatae species group and is morphologically related to A. angustiarum and A. impressa, but differs from these species in some features of leaves, inflorescences and infructescences. Its conservation status was assessed as Endangered (EN). Additionally, morphological evidence was provided in support of A. arcedianoensis as a species distinct from A. angustiarum. A key to morphologically and geographically closely related species in the Marginatae group is presented.